The Dramatic Structure Analysis of Wayang Kancil Play Sombong Kobong As A Means of Developing Pancasila Values - Sulaksono, Djoko; Kurwidaria, Favorita; Fitria, Rizki Ratda (International Journal of Multidisciplinary Sciences, 2025)
Wayang kancil is a type of wayang in Indonesia where the main play is about animal. This kind of wayang as one of communication media is used to teach audiences, especially children, moral values. Recently, wayang kancil is rarely performed. It is no longer existent since it is only performed in special occasions such as Hari Wayang Dunia and Temu Dalang Bocah Nusantara. Hence, the researchers aim to analyze wayang kancil purposely on the play known as Sombong Kobong. This article intends to scrutinize the dramatic structure of Sombong Kobong as well as to study the comprised Pancasila values. This study was a descriptive qualitative study involving a structural approach. The data were collected from documents and interviews transcripted from the reliable informants. The findings show that wayang kancil the play Sombong Kobong has a complete and clear dramatic structure that ease the audiences to figure out the story and the moral value. Furthermore, it embodies the Pancasila values that are applicable in the social life. Thus, wayang kancil is an art that personifies moral values. Wayang kancil can be more frequently performed and used as a teaching material for schools so that it is well preserved. By preserving wayang kancil, we preserve a noble culture.